Concordance in a World without a Gold Standard: A New Non-Invasive Methodology for Improving Accuracy of Fibrosis Markers - Poynard, Thierry (Public Library of Science, 2008)
BACKGROUND: Assessing liver fibrosis is traditionally performed by biopsy, an imperfect gold standard. Non-invasive techniques, liver stiffness measurements (LSM) and biomarkers [FibroTest® (FT)], are widely used in countries where they are available. The aim was to identify factors associated with LSM accuracy using FT as a non-invasive endpoint and vice versa. METHODS: The proof of concept was taken using the manufacturers recommendations for excluding patients at high risk of false negative/positive. The hypothesis was that the concordance between LSM and FT, would be improved by excluding high-risk patients. Thereafter, the impact of potential variability factors was assessed by the same methods. Liver biopsy and independent endpoints were used to validate the results. RESULTS: Applying manufacturers' recommendations in 2,004 patients increased the strength of concordance between LSM and FT (P<0.00001). Among the 1,338 patients satisfying recommendations, the methodology identified a significant LSM operator effect (P = 0.001) and the following variability factors (all P<0.01), related to LSM: male gender, older age, and NAFLD as a cause of liver disease. Biopsy confirmed in 391 patients these results. CONCLUSION: This study has validated the concept of using the strength of concordance between non-invasive estimates of liver fibrosis for the identification of factors associated with variability and precautions of use.